Contextual Teaching Learning; An Approach to Improving Students’ Mathematics Learning Outcomes - Fathurrahman, Fathurrahman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is motivated by the low level and lack of student activity in mathematics learning, where students tend to be relaxed and less motivated when learning takes place. This research was conducted in the form of Classroom Action Research with the research subjects being 36 class IV students at SD Negeri 21 Kota Bima. The aim of this research is to determine the improvement in student learning outcomes by using the Contextual Teaching Learning approach in mathematics subjects. The data used in this research is quantitative data obtained from teacher and student activities through observation, test questions on daily tests. The results of this research show that the average percentage of teacher activity during learning activities increased from 77.02% in cycle I, to 87.61% in cycle II. And the average percentage of student activity during learning activities increased from 83.93% in cycle I to 92.86% in cycle II. The average student learning outcomes seen from the test results have increased from the Basic Score obtained on average 69.73%. In the first daily test, it increased 4.8 points to 74.53%. And in the second daily test it increased again by 9.12 points to 83.73%. Overall, it can be concluded that the application of the Contextual Teaching Learning approach can improve the learning outcomes of class IV students at SD Negeri 21 Kota Bima.